Molecular analysis of pancreatic acinar cell cystadenomas: Evidence of a non‑neoplastic nature - Bergmann, Frank; Aulmann, Sebastian; Welsch, Thilo; Herpel, Esther; Schirmacher, Peter (Oncology letters, 2014)
The biology of pancreatic acinar cell cystadenomas has not been clearly defined. However, a non‑neoplastic process, caused by a cell differentiation failure leading to a cystic transformation, has been discussed, as well as a benign neoplastic lesion. Pancreatic acinar cell cystadenomas usually consist of thin‑walled unilocular or multilocular cysts, and mural nodules have been described in two cases of a recent series. In one of these nodules, chromosomal imbalances were detected, which provided preliminary evidence for a neoplastic process. The aim of the current study was to further characterize the lesions by molecular analyses. In four cases without mural nodules, the clonality was assessed by performing mutational analyses within the highly variable displacement‑loop region of the mitochondrial DNA. As a result, no closer correlation was identified between different foci within the tumors than between the tumors and adjacent normal pancreatic acinar tissue, indicating polyclonality of these lesions. Further molecular analyses revealed no mutations of the β‑catenin and K‑ras genes. In addition, no immunohistochemical evidence was identified for mutations of Smad4 or p53. In conclusion, the results of the current study demonstrated that pancreatic acinar cell cystadenomas are non‑neoplastic lesions, with the potential exception of those rare cases with mural nodules.